Help yourself with single-session therapy - Dryden, Windy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Help Yourself with Single-Session Therapy provides an outlook on how you can help yourself with your emotional problems by using insights from single-session therapy. Single-Session Therapy draws upon the skills and strengths of both the therapist and the client. The book will encourage you to develop your own solutions to your problems. Broken down into fourteen accessible chapters, it will help you to identify the problem before guiding you to provide your own goals and solutions. The importance of how to maintain change is also a key part of the process. Help Yourself will be useful for all those who wish to help themselves with their emotional problems and for those who wish to support them. It will also be relevant for counsellors, psychotherapists and students in these disciplines who are interested in the application of very-brief therapy to self-help"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Single-session psychotherapy; Psychotherapist and patient; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health